Culture-Specific Observations in a Saudi Arabian Digital Home Health Care Program: Focus Group Discussions With Patients and Their Caregivers - Abdulaziz A Alodhayani; Marwah Mazen Hassounah; Fatima R Qadri; Noura A Abouammoh; Zakiuddin Ahmed; Abdullah M Aldahmash (JMIR Publications, 2021)
BackgroundThere is growing evidence of the need to consider cultural factors in the design and implementation of digital health interventions. However, there is still inadequate knowledge pertaining to the aspects of the Saudi Arabian culture that need to be considered in the design and implementation of digital health programs, especially in the context of home health care services for patients who are chronically and terminally ill. ObjectiveThis study aims to explore the specific cultural factors related to patients and their caregivers from the perspective of physicians, nurses, and trainers that have influenced the pilot implementation of Remotely Accessible Healthcare At Home, a connected health program in the Home Health Care department at King Saud University Medical City, Riyadh, Saudi Arabia. MethodsA qualitative study design was adopted to conduct a focus group discussion in July 2019 using a semistructured interview guide with 3 female and 4 male participants working as nurses, family physicians, and information technologists. Qualitative data obtained were analyzed using a thematic framework analysis. ResultsA total of 2 categories emerged from the focus group discussion that influenced the experiences of digital health program intervention: first, culture-related factors including language and communication, cultural views on using cameras during consultation, nonadherence to web-based consultations, and family role and commitment and second, caregiver characteristics in telemedicine that includes their skills and education and electronic literacy. Participants of this study revealed that indirect contact with patients and their family members may work as a barrier to proper communication through the Remotely Accessible Healthcare At Home program. ConclusionsWe recommend exploring the use of interpreters in digital health, creating awareness among the local population regarding privacy in digital health, and actively involving direct family members with the health care providers.